2018
DOI: 10.1186/s41687-018-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel observer-reported outcome measure for the assessment of Respiratory Syncytial Virus (RSV) infection symptoms in pediatric clinical trials

Abstract: BackgroundRespiratory syncytial virus (RSV) is a seasonal infection affecting most children by 2 years of age and the leading cause of lower respiratory tract infection requiring hospitalization in infants. Novel antiviral medications are in development to improve the clinical outcomes of RSV; however, no clinical outcome assessments (COAs) for RSV have been developed in alignment with the United States Food and Drug Administration patient-reported outcome guidance to assist in the evaluation of new therapies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The majority of identified studies were conducted after 2000 (n=15, 83.3%), including 10 studies (66.6%) published in the last 4 years. 10 were undertaken in Europe [ 14 , 15 , 18 , 19 , 25 27 ], two in Asia [ 16 , 20 ] and four in North America [ 7 , 11 , 13 , 17 ]. Two were conducted in more than one country [ 12 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of identified studies were conducted after 2000 (n=15, 83.3%), including 10 studies (66.6%) published in the last 4 years. 10 were undertaken in Europe [ 14 , 15 , 18 , 19 , 25 27 ], two in Asia [ 16 , 20 ] and four in North America [ 7 , 11 , 13 , 17 ]. Two were conducted in more than one country [ 12 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Children's age groups were well represented: 11 studies were conducted in children 0–14 months old; 11 articles in children 15–59 months old; and nine articles in children aged 60–216 months old ( supplementary material 2 ). Studies were conducted in children with a broad spectrum of ALRIs, ranging from RSV-associated bronchiolitis (n=5) [ 13 , 17 , 18 , 20 , 21 ], influenza (n=6) [ 11 , 12 , 14 , 15 , 25 , 27 ], bronchitis (n=1) [ 23 ], community-acquired pneumonia (n=2) [ 24 , 26 ], ALRI (n=1) [ 19 ] and unspecified respiratory infections (n=4) [ 7 , 16 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings echo other recent studies in which ObsROs for assessing child health have been tested. Williams et al, found that caregivers were able to reliably report signs of respiratory syncytial virus infection and that reports generally had acceptable construct validity and were responsive to change (Lewis et al, 2017; Williams et al, 2017). Similarly, Edwards et al (2018) found that caregivers of young children (ages 0-6 years) with cystic fibrosis could reliably report respiratory signs that discriminated between well and sick periods.…”
Section: Discussionmentioning
confidence: 99%